Relationship between Skinfolds and Bioelectric Impedance in Determining Percent Body Fat - Tsiokanos, Αθανάσιος Λ.; Jamurtas, Αθανάσιος Ζ.; Theodoratou, Ελένη; Verigakis, Ιωάννης; Giotsopoulou, Ελένη; Tsaopoulos, ∆ηµήτριος (Inquiries in Physical Education and Sport, 2003)
The purpose of this study was to examine the relationship between the skinfolds method and two different methods of bioelectrical impedance (BIA) in determining the percent body fat. One of the two methods of BIA was based on the two contact points (TANITA) and the second one was based on the four contact points (BODYSTAT). The subjects in the study were 90 males and were separated into three groups (30 students, 30 basketball players and 30 swimmers) and their body mass and height (mean ± SD) was 78.2 ± 13.6 Kg and 180.6 ± 8.3 cm. The percent body fat values for the population sample measured by the skinfolds method, TANITA and BODYSTAT were 10.98 ± 4.87, 12.68 ± 5.74 and 15.34 ± 5.54, respectively. The correlation coefficients between TANITA and skinfolds and BODYSTAT and skinfolds were r = .63 and r = .64, respectively. However, when the evaluation was performed separately on the three different groups the correlation coefficients between the skinfolds and TANITA and skinfolds and BODYSTAT were r = .82 and r =.62 for the students, r = .81 and r = .72 for the basketball players, and r = .85 and r = .53 for the swimmers. Based on the differences on the correlation coefficients that were found in the three different groups, it seems that TANITA correlates better in identifying the percent body fat with the skinfolds method compared to BODYSTAT. In addition, the homogeneity of the sample is an issue that needs to be examined before using the BIA method to determine the percent body fat.